Randomised controlled trial to assess the impact of hospital–community pharmaceutical care on drug-related problems in oncology practice for at-risk outpatients treated with oral anticancer drugs—a French Society for Oncology Pharmacy (SFPO) study: DROP-SFPO study protocol - Patrick Tilleul; Christophe Bardin; Bertrand Pourroy; Florence Ranchon; Catherine Rioufol; Laure Huot; Isabelle Madelaine; Jean Louis Cazin; François Lemare (BMJ Open)
Introduction Drug-related problems (DRPs) associated with oral anticancer drugs are frequent and require a new healthcare organisation to manage them on an outpatient basis. The aim of this article is to present the study protocol of the Drug Related problems in Oncology Practice (DROP) randomised controlled trial (RCT), endorsed by the French Society for Oncology Pharmacy. The main objective of the DROP RCT is to measure the impact at 6 months of the DROP community/hospital pharmaceutical intervention programme, compared with usual treatment, on the mean number of DRP (ie, adverse effects, drug–drug interactions, medication errors) related to oral anticancer drugs in at-risk outpatients.Methods and analysis The DROP protocol is a prospective, multicentre controlled clinical trial, with individual randomisation, comparing in parallel and in open, two groups of outpatients treated with oral anticancer drugs. The interventional group benefits from the DROP multidisciplinary intervention on oral anticancer treatment. The control group receives usual care. The primary outcome of the DROP RCT is the number of DRP due to oral anticancer drugs, per patient, identified between the inclusion of the patient and 6 months after inclusionEthics and dissemination Approval to conduct this study was obtained for all participating centres from an Ethics Committee (Comité de Protection des Personnes Sud-Méditerranée V) in August 2018 in accordance with French law. The trial results will be disseminated at clinical conferences and published in peer-reviewed journals.Trial registration number ClinicalTrials.gov: NCT03257969, recruitment started in June 2019. The current protocol version is V.9, 13 December 2023.